2001
DOI: 10.1093/jn/131.2.325
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Nutrient Intakes among Pregnant Women in Indonesia: Implications for the Design of Epidemiological Studies Using the 24-h Recall Method

Abstract: Few studies have assessed the reliability of dietary intake methods during pregnancy. Between 1996 and 1998, a longitudinal study of dietary intake during pregnancy was carried out among 451 women in Central Java, Indonesia. Six 24-h recalls were performed each trimester. We report here on intraindividual and interindividual variability in energy and nutrient intakes, as well as the reliability of the 24-h diet recall method. Implications of the use of different numbers of replicate days for estimating dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 21 publications
2
23
0
6
Order By: Relevance
“…This suggests that it would be more difficult to detect a statistically significant association between micronutrients intake, given the langer error associated with the estimation of micronutrient intakes. 33,34 Hence, small increases of energy that are found are not due to measurement errors. This is confirmed by the contrast between the relatively high mean BMI of this population and the low average reported adequacy of energy intake (approximately 55%).…”
Section: Discussionmentioning
confidence: 78%
“…This suggests that it would be more difficult to detect a statistically significant association between micronutrients intake, given the langer error associated with the estimation of micronutrient intakes. 33,34 Hence, small increases of energy that are found are not due to measurement errors. This is confirmed by the contrast between the relatively high mean BMI of this population and the low average reported adequacy of energy intake (approximately 55%).…”
Section: Discussionmentioning
confidence: 78%
“…The lack of association between dietary intakes and vitamin A deficiency might be due to the lack of precision of a single 24-h recall; there is a need for 6 recalls obtaining a precision of ± 20%. 34 It is noteworthy that the public health programs administered by the Mexican health authorities include the administration of an oral macro dose of vitamin A, twice yearly, to children <2 years of age who live in depressed socioeconomic areas. This might contribute to the low prevalence of vitamin A deficiency in small children; however, the effectiveness of such a program has not been evaluated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Others have suggested that three 24 h dietary recalls were best for estimating energy intake in normalweight women (9) . The number of days that dietary intake should be collected can be determined by estimating within-subject variance, which is the day-to-day variation in each individual's nutrient intake, and between-subject variance, which is the extent that individuals' nutrient intake varies from one another (10)(11)(12)(13)(14)(15)(16) . Several factors such as sex, day of the week, season, culture and environment influence nutrient variation (17)(18)(19) .…”
mentioning
confidence: 99%